ANALYSIS OF THE E-PERFORMANCE ASSESSMENT SYSTEM, COMMUNICATION AND WORK STRESS ON THE PERFORMANCE OF STATE CIVIL APPARATUS AT THE DEVELOPMENT PLANNING AND RESEARCH AGENCY OF SURAKARTA CITY - Jarwati, Jarwati; Hartono, Sri; Djumali, Djumali (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
This research aims to analyze and know the effect of simultaneous or partial assessment of the system of performance, communication and stress of work on the performance of civil apparatus in the state of the Development Planning and research agency of the Surakarta city. The type of research used is quantitative research a descriptive method. The type and source of data used is the main data collected and processed by the researchers of the object. The number of population in this study is the entire civil apparatus of the state in the Bappeda area of Surakarta which amounted to 45 people and the technique of sample used is a total sampling that uses formula Slovin. The Data is collected using a poll method of 45 people in this study. The data analysis techniques used in this study were data quality tests, classical assumption tests, double linear regression tests, F tests, T tests and coefficient determination with the help of SPSS software program version 21.0. The results of this study showed that working stress was negatively and significantly influential on employee performance, while the E- performance system of and communication had significant effect on the BAPPEDA performance of Surakarta. Keyword; employee performance, communication, stress of work, E-performance system